A review on sustainability assessment of fuel cell electric vehicles - Zhensen Ding; Lingjun Song; Haifeng Fang; Zhanhui Yao (Transportation Research Interdisciplinary Perspectives)
The use of fuel cell electric vehicles (FCEVs) is increasingly recognized as a vital strategy for achieving comprehensive decarbonization in the transportation industry. However, research on the sustainability of FCEVs remains limited. The assessment of their sustainability is complicated and contentious due to the absence of a universally accepted methodology for sustainability analysis. This study conducted a thorough literature review, identifying 135 studies related to the sustainability of FCEVs within the Web of Science (WoS) and Scopus databases, covering the years 2012 to 2024. The identified studies encompassed environmental, economic, and social dimensions of sustainability. The investigation systematically assessed critical components of sustainability analysis methodologies, including impact indicators, life cycle stages, and life cycle inventories. Furthermore, a novel research framework for sustainability analysis was proposed. Using this framework, the study examined the sustainability of FCEVs and conducted an in-depth analysis of two pivotal factors: the technical pathway and durability. The results indicate that essential elements, such as system boundaries, inventory analysis, and impact assessment within the sustainability research methodology for FCEVs, continue to encounter significant challenges. The adoption of a holistic evaluation approach may enhance the development of a sustainability research framework. According to the framework presented in this study, FCEVs exhibit considerable potential for sustainability. Existing research has explored the effects of various technological pathways on vehicle structure, fuel cell types, electrical architecture, and key components, as well as the implications of durability.